2019
DOI: 10.3390/su11195400
|View full text |Cite
|
Sign up to set email alerts
|

Backyard Agricultural Production as a Strategy for Strengthening Local Economy: The Case of Chontla and Tempoal, Mexico

Abstract: In order to define chain strategies for a backyard agricultural production system, this study identified agricultural products produced by high development priority communities with indigenous presence located in the Chontla and Tempoal municipalities in Veracruz, Mexico. The production system was integrated into a generic model decomposing the supply chain into hierarchical components. Data were collected through a face-to-face semistructured questionnaire based on statistical sampling of rural households, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…and support the daily sustenance of their homes 31 . The "Foro Nacional de Nopal, Tuna y Maguey" indicated that the wasted matter of cladodes and its products have sufficient potential to generate income for Mexicoʼs agricultural gross domestic product (PIB) and have a high economic potential [19][20][21] .…”
Section: Degree Of Methyl Esterification Of Mucilage Ofmentioning
confidence: 99%
“…and support the daily sustenance of their homes 31 . The "Foro Nacional de Nopal, Tuna y Maguey" indicated that the wasted matter of cladodes and its products have sufficient potential to generate income for Mexicoʼs agricultural gross domestic product (PIB) and have a high economic potential [19][20][21] .…”
Section: Degree Of Methyl Esterification Of Mucilage Ofmentioning
confidence: 99%
“…López- Sánchez et al (2019) present a hybrid algorithm as a solution method to the p-median model, which consists of combining two metaheuristics (GRASP) which is a greedy random adaptive search procedure, and a variable neighborhood search algorithm (VNS), finding that when solving a complete set of instances with different sizes, the hybrid GRASP_VNS algorithm obtains better solutions than the VNS algorithm or GRASP algorithm separately. Hu and Dong (2019) present a stochastic programming model for the location of facilities with inventory and selection of suppliers considering the different discounts offered according to the order quantity and the required delivery time, in order to generate different alternatives to help humanitarian, highlighting the importance of establishing a close relationship with suppliers for the supply of first aid items.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The aim is to segment a municipality into rural production micro-regions, for the inclusion of backyard agricultural producers into short-commercialization circuits as a strategy for strengthening the local economy (Sánchez-Galván et al, 2019) and as a learning mechanism that allows identifying the elements that determine territorial development. It can hypothesize that this study will contribute to establishing inclusive agro-food shorts chains for creating resilience in agricultural economic activities.…”
Section: Introductionmentioning
confidence: 99%